2002
DOI: 10.1159/000058395
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Soluble CD26 and CD30 in Patients on Hemodialysis

Abstract: Background/Aims: Various abnormalities of the immune system have been demonstrated in patients on hemodialysis (HD). We hypothesize that the imbalance between type 1 helper T (Th1) cells and type 2 helper T (Th2) cells in patients on HD contributes to these abnormalities. Furthermore, we investigate the relationship between the Th1/Th2 imbalance and HD duration. Methods: We measured the serum levels of soluble CD26 (sCD26) and soluble CD30 (sCD30) in 47 patients on HD and in 13 patients with chronic renal fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…suggested that a significant intrathecal Th1 response associated with CD26 expression develops during relapse in RNMO 18 . The Th1/Th2 balance may shift towards Th2 dominance in patients on hemodialysis (HD) by analysis of the serum sCD26 levels 19 . By contrast, another study which was carried out on allergic asthma patients showed a role of CD26 in the Th2‐type immunity 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that a significant intrathecal Th1 response associated with CD26 expression develops during relapse in RNMO 18 . The Th1/Th2 balance may shift towards Th2 dominance in patients on hemodialysis (HD) by analysis of the serum sCD26 levels 19 . By contrast, another study which was carried out on allergic asthma patients showed a role of CD26 in the Th2‐type immunity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the aberrant expression of CD26 is induced by stimuli of the Th1 response 7,14 . Further, the level of sCD26 is detected in some disorders in correlation with the Th1 response 15–20 . By contrast, other studies demonstrated that CD26 may contribute to the dominant Th2‐type immunity 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…The uremia itself and the ESRD induce activation of T-cells and the expression of CD30 [10,11]. Some investigators have also shown that serum creatinine level does not influence the sCD30 level [10,12]. Thus, immunosuppression and normalization of serum creatinine can be the cause of the deceasing trend in sCD30 level.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, during renal insufficiency, the proteolytic activation of CCL14a(9 -74) from CCL14a(1-74) exceeds the capacity of the CCL14a(9 -74)-inactivating pathways and may be correlated to the slow kinetics that have been found for the proteolytic inactivation of CCL14a(9 -74) by CD26/DPPIV and APN. An increase in the plasma concentration of CCL14a(9 -74) during renal insufficiency has been suggested by a rise in the concentration of CCL14a and its activating protease, uPA, in the plasma of these patients (41)(42)(43), whereas the plasma concentrations of APN and CD26/DPPIV are not significantly increased during renal insufficiency (44,45). In hemodialysis, patients also experience an increase in other chemokines.…”
Section: Proteolytic Inactivation Of Ccl14amentioning
confidence: 99%